The Human Cathelicidin Antimicrobial Peptide LL-37 as a Potential Treatment for Polymicrobial Infected Wounds - Duplantier, Allen J.; van Hoek, Monique L. (Frontiers in Immunology, 2013)
Diabetic patients often have ulcers on their lower-limbs that are infected by multiple biofilm-forming genera of bacteria, and the elimination of the biofilm has proven highly successful in resolving such wounds in patients. To that end, antimicrobial peptides have shown potential as a new anti-biofilm approach. The single human cathelicidin peptide LL-37 has been shown to have antimicrobial and antibiofilm activity against multiple gram-positive and gram-negative human pathogens, and have wound-healing effects on the host. The combination of the anti-biofilm effect and wound-healing properties of LL-37 may make it highly effective in resolving polymicrobially infected wounds when topically applied. Such a peptide or its derivatives could be a platform from which to develop new therapeutic strategies to treat biofilm-mediated infections of wounds. This review summarizes known mechanisms that regulate the endogenous levels of LL-37 and discusses the antibiofilm, antibacterial and immunological effects of deficient versus excessive concentrations of LL-37 within the wound environment. Here, we review recent advances in understanding the therapeutic potential of this peptide and other clinically advanced peptides as a potential topical treatment for polymicrobial infected wounds.